2021
DOI: 10.1063/5.0041894
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the binding behavior of graphene oxide and noble metal nanoparticles

Abstract: The binding behavior of graphene oxide and metal nanoparticles (Au, Pt, and Pd) was observed by UV–Vis spectroscopy, fluorescence spectroscopy, dynamic light scattering, and zeta potential. Hybrids with a fixed concentration of graphene oxide (GO) were prepared with increasing concentration of metal nanoparticles to observe the effect of binding on their spectroscopic properties, size, and zeta potential. An increase in the absorption spectra of GO after binding with nanoparticles and a gradual decrease in flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Additionally, the oxidation rate of graphene nanosheets plays a crucial role in controlling energy level confinement to different degrees, which ultimately affects the FE of GO. 46,51,52…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the oxidation rate of graphene nanosheets plays a crucial role in controlling energy level confinement to different degrees, which ultimately affects the FE of GO. 46,51,52…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the oxidation rate of graphene nanosheets plays a crucial role in controlling energy level connement to different degrees, which ultimately affects the FE of GO. 46,51,52 As previously described, citrate ions along with the GO's oxygen moieties can assist in the prolonged stabilization of AgNPs on the GO nanosheet. Briey, the overlaying of the anions around the AgNP's surface creates strong electrostatic repulsion that allows uniform AgNPs distribution on the GO sheet.…”
Section: Plausible Detection Principle Of Malaoxon Using Ache-atch-ag-gomentioning
confidence: 89%
“…[31] In our case, while plotting the concentration of GQD against F 0 /F and τ 0 /τ a nonlinearity is observed for both GQD-TPP and GQD-TNaP nanohybrids and that is a portrayal of combined static and dynamic quenching. [32,33] From the earlier reports it is concluded that there is a nonradiative electron transition that occurs from excited porphyrins to GQDs, which competes with the fluorescence of PPys. [34] This non-radiative rate constant, k nr is the comparison between the lifetime values of TPP and TNaP in the absence of GQD (τ o ) and presence of GQD (τ) as in equation 7.…”
Section: Lifetime Analysismentioning
confidence: 99%
“…Hybrids of MNPs and graphene nanomaterials (GNMs) like GO, graphene quantum dots (GQDs) and reduced graphene oxide (rGO), because of their synergistic properties, find application in sensors [ 8 , 9 ], electronics [ 10 ], biomedicine [ 10 ], energy conversion [ 11 ], catalysis [ 10 ], and in removal of environmental pollutants [ 12 ], depending on the MNPs composition. For example, hybrids of GO and plasmonics have unique properties including high specific surface area, chemical and electrochemical inertness which suit them for use in biosensors and surface enhanced Raman spectroscopy (SERS) for early stage medical conditions diagnosis [ 13 ]. This review focuses on applying MNPs and hybrids of MNPs/(GNMs) in PSCs and DSSCs.…”
Section: Introductionmentioning
confidence: 99%